Sexual dysfunction in patients with myocardial infarction - (:unkn) unknown (My University, 2004)
OBJECTIVE: This study has been performed in order to define the prevalence of sexual dysfunction (SD) in patients with myocardial infraction (MI), and to identify potential correlations between sexual dysfunction and socio-demographical attributes, cardio-vascular diseases, and factors that pose risks for SDs, as well as to define whether there is a relationship between sexual dysfunction and quality of life. METHODS: In this study, which was carried out with a total of 102 patients with MI (36 women, 66 men), the data were gathered via an information form that assesses socio-demographical attributes and risk factors related to cardiovascular diseases and sexual dysfunction; international sexual dysfunction assessment forms; Short Sexual Index Inventory for women (IFSF); Erection Function International Assessment Form (IIEF) for men; and SF-36 Quality of Life Scale. Obtained data were evaluated using statistical evaluations, Student t-test, Chi-square, Fisher precise Chi-square, Yates corrected Chi-square, and Pearson correlation tests. RESULTS: Sexual dysfunction was defined in 80% of women, and 37% of men. Its prevalence was higher than expected in women. Reductions in the frequency of intercourse and sexual satisfaction were reported by 53.9% and 32.4% subjects, respectively. The most important reason associated with the decreased prevalence of sexual intercourse was the fear of re-infarction, with a rate of 85.5%. All quality of life sub-dimension scores, other than social functioning (p>0.05), were low showing statistical differences. Of the subjects, 97.1% were not given information before being discharged. On the other hand, only 57.8% of them desired to be informed on the subject. CONCLUSION: Sexual dysfunction prevalence is high in patients with MI history; SD is more frequent in women than in men, and the patients are not assessed on this aspect.
Keywords: Adult; Female; Humans; Middle Aged; Surveys and Questionnaires; Quality of Life; Aged; Turkey; Prevalence; Male; Risk Factors; Myocardial Infarction; Demography; Sexual Dysfunctions, Psychological